2020
DOI: 10.1016/j.neurobiolaging.2019.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity among brain regions affected in Alzheimer's disease is associated with CSF TNF-α in APOE4 carriers

Abstract: It is now recognized that understanding how neuroinflammation affects brain function may provide new insights into Alzheimer’s pathophysiology. Tumor necrosis factor (TNF)-α, an inflammatory cytokine marker, has been implicated in Alzheimer’s disease (AD), as it can impair neuronal function through suppression of long-term potentiation. Our study investigated the relationship between cerebrospinal fluid TNF-α and functional connectivity (FC) in a cohort of 64 older adults (μ age = 69.76 years; 30 cognitively n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 92 publications
1
23
0
1
Order By: Relevance
“…Regarding functional connectivity in the EEG/MEG signals in patients with AD, many previous studies have reported a reduction in functional connectivity at the alpha, beta, and gamma bands (38,45,46,64). Further, recent studies of AD pathology have revealed that the reduction in functional connectivity is caused by neuroinflammation and deposition of amyloid-b and tau proteins (65)(66)(67). Similar reductions in functional connectivity were also observed in this study.…”
Section: Resultssupporting
confidence: 88%
“…Regarding functional connectivity in the EEG/MEG signals in patients with AD, many previous studies have reported a reduction in functional connectivity at the alpha, beta, and gamma bands (38,45,46,64). Further, recent studies of AD pathology have revealed that the reduction in functional connectivity is caused by neuroinflammation and deposition of amyloid-b and tau proteins (65)(66)(67). Similar reductions in functional connectivity were also observed in this study.…”
Section: Resultssupporting
confidence: 88%
“…Serum concentrations of TNF-α are also found to be upregulated in AD and in MCI 34 , and increased TNF-α serum levels have an associated four-fold greater rate of cognitive decline than AD patients with low baseline TNF-α 35 . Elevated cerebrospinal fluid (CSF) levels of TNF-α have positively correlated with APOE4 status and decline in functional connectivity between regions of the brain involving memory, language, and higher decision making 36 . Collectively, these studies suggest an enduring link between high serum and CSF TNF-α levels, inflammation, and progressive cognitive decline in AD.…”
Section: Resultsmentioning
confidence: 99%
“…In corroboration of a role for TNF-α in AD, a strong association between elevated TNF-α levels and decreased functional connectivity in an AD susceptible cohort has been observed at a whole-brain level (34). Aside from TNF-α as a consistently elevated proin ammatory marker in AD, its regulation of the NF-κB in ammatory cascade is well characterized (35,36).…”
Section: Discussionmentioning
confidence: 92%